2014
DOI: 10.1089/jpm.2013.0374
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning: Challenges and Approaches for Pediatricians

Abstract: We hope that acknowledgement of some of the challenges, alongside recognition of the clear benefits, of planning will help pediatricians to deliver this important area of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 15 publications
4
34
0
Order By: Relevance
“…In a recent study in the UK, authors found that in one in four children with a life-threatening or life-limiting condition, there was no advanced care plan, and almost half of all patients and their families were not offered a choice regarding location of care in the last months of life and location of death 17. The lack of this advanced care plan implies important decisions might be made later, on an ad hoc basis and the risk of time and/or emotional pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in the UK, authors found that in one in four children with a life-threatening or life-limiting condition, there was no advanced care plan, and almost half of all patients and their families were not offered a choice regarding location of care in the last months of life and location of death 17. The lack of this advanced care plan implies important decisions might be made later, on an ad hoc basis and the risk of time and/or emotional pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Countries such as the UK are leading the way in paediatric palliative care, with enhanced integration within the health care system and well‐established and effective guidelines and resources to assist in advanced care planning for children (Finlay et al . ; Heckford & Beringer ; Xafis et al . ,).…”
Section: Discussionmentioning
confidence: 99%
“…Palliative care benefits these children and families by providing expert symptom management, care coordination and supportive counselling, including advanced care planning (Graham & Robinson ; Miller et al . ; Heckford & Beringer ; Schwantes & O'Brien ). Early integration of paediatric palliative care is recommended by national organizations for a variety of paediatric illnesses and has been shown to be feasible and acceptable (Department of Health ; Mack & Wolfe ; American Academy of Pediatrics ; American Academy of Pediatrics, Section on Hospice and Palliative Medicine and Committee on Hospital Care ; Berlinger et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations